Optimalisasi Terapi Aktivitas Kelompok untuk Meningkatkan Kemandirian Lansia dalam Pemenuhan Activity Daily Living (ADL) di PPSLU Mappakasunggu Pare-pare - Hasifah Hasifah; Amriati Mutmainna; Erna Kadrianti; Maryam Jamaluddin; Alfiah Alfiah (Jurnal Pengabdian Bidang Kesehatan, 2024)
Elderly people living in nursing homes often experience various challenges, such as physical limitations, loneliness, and decreased cognitive and psychosocial functions. One approach that can be applied to improve the welfare and independence of the elderly is Group Activity Therapy (GAT). The purpose of community service is to help the elderly increase their independence in fulfilling Daily Living (ADL) activities with Group Activity Therapy. The method of implementing the activity is carried out with a pre-test - post-test using a questionnaire. The elderly are given counseling then Group Activity Therapy. This activity was carried out on Saturday, December 14, 2024 at PPSLU Mappakasunggu Pare-pare. This activity was attended by 32 elderly people. The results of the pre-test elderly independence level were 62.5% elderly with dependence and 37.5% elderly with independence while the post-test independence level was 43.75% elderly with dependence and 56.25% with independence. To PPLSU Mappakasunggu Pare-pare to facilitate group activity therapy (TAK) continuously to create a feeling of joy so that the quality of life of the elderly remains healthy, independent, useful and productive.